Social interactions in coworking spaces : Case Study of Prague-based coworking spaces - Pavlova, Zhanna; Orel, Marko, 1986-; Mayerhoffer, Manuel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
The thesis is based on the idea of the topic of social interactions in coworking spaces. The first part of the work will be devoted to the theoretical overview, i.e. the description is social interaction itself to understand its nature, characterization of coworking spaces and its importance, usefulness, and applicability. The second part will be dedicated to the practical representation of the topic and research. Consequently, to show valuable and relevant results I will use the qualitative methods for collection of the data, which in turn means interviews with the members of coworking spaces and analysis of the gathered data. It will give the possibility to see the situation from different points of view, understand what plays a significant role in interaction in this type of working space, and at the same time to recognize advantages and disadvantages of coworking spaces when it comes to communication between coworkers in such environment.
Vedoucí práce: Marko Orel
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses